Scholarly Communications Training: Professional Development for the Next Generation of Scholars - Craft, Anna R.; Harlow, Samantha (Serials review, 2020)
Many campuses are seeing increased needs for support in scholarly communications areas such as open access, research identity management, scholarship metrics, and related topics. This article discusses a professional development program that addresses scholarly communications needs for online and in-person graduate students and faculty at UNC Greensboro (UNCG), through a collaborative, interdepartmental effort that brings together librarians from the departments of Research, Outreach, and Instruction (ROI) and Technical Services. The authors provide a brief overview of the literature related to scholarly communications needs and training in academic libraries and discuss the UNCG program's inception, modules, format, assessment, and future directions.